Pengaruh Model Teams Games Tournament Bernantuan Media Powtoon Terhadap Hasil Belajar Tematik Peserta Didik Kelas V SDN Kraton (Eduscotech, 2022)
The problem in this research is the low thematic learning outcomes of fifth-grade students at SDN Kraton. The purpose of this study was to determine the significant effect of the application of the Teams Games Tournament learning model assisted by Powtoon media. This research method is a quasi-experimental research design with a quasi-experimental design. The total population of this study was 42 students. The number of samples in this study was 42 students. The sampling technique used a non-probability sampling technique with a total of 42 students. Data collection techniques in this study used tests and non-tests in the form of documentation and observation. Data analysis used a simple linear regression test. The results showed that there was a significant influence on the application of the powtoon-assisted team's games tournament learning model in the form of increasing the thematic learning outcomes of students in the experimental class after being treated using the powtoon-assisted team's games tournament model.